Ethics of Business Practices - Jawabreh, Raneem Z. (PROSPECTIVE RESEARCHES, 2024)
This study aims to identify the importance of the ethics of business practices because of their role in advancing the development and economic growth of all countries and to determine what are the right and wrong practices. The study uses the descriptive approach, and among the results of this study is that the nature of the company’s work and business practices affect the ethics of its individuals. Applying ethics at work reduces risks, and among the recommendations of this study is strengthening the culture of society and economic development towards ethics in business practices